Is Internet the Next Printing press? Theoretical Elements to Explore Internet’s Socio-Cultural Process - Vega Chin, Rebeca (2012)
This essay results from the analysis of diverse authors to support the dissertation Internet’s socio-cultural process on non-specialized persons (NSP): the support of daily routines. Internet is used differently according to how it supports people’s daily routines. The concepts developed by the authors allow the deconstruction of Internet’s socio-cultural process in order to analyze it. The changes caused by digital media may be compared with the consequences brought by the development of the printing press.